2017
DOI: 10.1098/rsob.170075
|View full text |Cite
|
Sign up to set email alerts
|

Caryolan-1-ol, an antifungal volatile produced byStreptomycesspp., inhibits the endomembrane system of fungi

Abstract: Streptomyces spp. have the ability to produce a wide variety of secondary metabolites that interact with the environment. This study aimed to discover antifungal volatiles from the genus Streptomyces and to determine the mechanisms of inhibition. Volatiles identified from Streptomyces spp. included three major terpenes, geosmin, caryolan-1-ol and an unknown sesquiterpene. antiSMASH and KEGG predicted that the volatile terpene synthase gene clusters occur in the Streptomyces genome. Growth inhibition was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Few studies have investigated this question, and disruption of cell membrane integrity and perturbation of redox balance are two commonly observed consequences of bacterial volatile exposure (Giorgio et al , ). Recently, the terpene caryolan‐1‐ol, commonly produced by Streptomyces spp., was reported to affect the endomembrane system of Botrytis cinerea b y disrupting sphingolipid synthesis and vesicle trafficking (Cho et al , ). More research efforts are needed to gain basic understanding on the molecular mechanisms underlying the observed effects of bacterial volatiles on the various plant pathogens.…”
Section: Indirect Effects Of Bacterial Volatiles On Plant Health: Affmentioning
confidence: 99%
“…Few studies have investigated this question, and disruption of cell membrane integrity and perturbation of redox balance are two commonly observed consequences of bacterial volatile exposure (Giorgio et al , ). Recently, the terpene caryolan‐1‐ol, commonly produced by Streptomyces spp., was reported to affect the endomembrane system of Botrytis cinerea b y disrupting sphingolipid synthesis and vesicle trafficking (Cho et al , ). More research efforts are needed to gain basic understanding on the molecular mechanisms underlying the observed effects of bacterial volatiles on the various plant pathogens.…”
Section: Indirect Effects Of Bacterial Volatiles On Plant Health: Affmentioning
confidence: 99%
“…The strain inhibited F. oxysporum in vitro , suppressed disease on strawberry, and produced a novel heat‐stable, ribosomally synthesized thiopeptide, conprimycin, a major factor in control of the pathogen that, based on chemogenomic analysis, interfered with cell wall organization and biogenesis, transcription, cytoskeleton organization, and RNA catabolism in the model yeast Saccharomyces cerevisiae . Further genetic dissection of the antifungal arsenal of S4‐7 has revealed that within its genome are 30 predicted secondary metabolite gene clusters including four lantipeptides, two bacteriocins, two siderophores, two butyrolactones, three NRPSs, six clusters encoding terpenes, two ectoines, three polyketide synthetases, four NRPSs linked to polyketide synthetases, one melanine cluster, and a lassopeptide cluster . Of these, the ribosomally synthesized and posttranslationally modified LanM lanthipeptide provisionally named grisin, contributed substantially to inhibition of the wilt pathogen and is the first class II lantipeptide from Streptomyces reported to have a biological function.…”
Section: Streptomyces: Long Sought Newly Recognized As ‘Plants’ Bestmentioning
confidence: 99%
“…In addition, the lanM gene itself has proven useful as a molecular probe for the presence in soils of populations of Streptomyces capable of mediating soil suppressiveness of the Fusarium wilt pathogen . Strain S4‐7 also produces three volatile terpenes, geosmin, caryolan‐1‐ol, and an unknown sesquiterpene, with caryolan‐1‐ol responsible for dose‐dependent inhibition of growth and sporulation of the strawberry foliar pathogen Botrytis cinerea . At the molecular level, caryolan‐1‐ol targeted cellular processes related to sphingolipid synthesis, vesicle transport, vesicle trafficking and maintenance in S. cerevisiae .…”
Section: Streptomyces: Long Sought Newly Recognized As ‘Plants’ Bestmentioning
confidence: 99%
See 2 more Smart Citations